BIOMETRIC AND REPRODUCTIVE INDICATORS IN Perna perna (Linnaeus, 1758) MUSSELS FROM COASTAL MARICULTURE IN RIO DE JANEIRO, BRAZIL: Indicadores biométricos e reprodutivos em mexilhões Perna perna (Linnaeus, 1758) de mariculturas costeiras no Rio de Janeiro, Brasil - de Freitas Guimarães Filho, Carlos Eduardo; Andrade Calixto, Flávia Aline; Kasnowski Holanda Duarte, Maria Carmela; Marques de Mesquita, Eliana de Fátima (Arquivos de Ciências do Mar, 2023)
The aim of this study was to analyze biometric and reproductive mussel indicators (Perna perna) from coastal maricultures in Rio de Janeiro, Brazil. The collections were carried out with a total of 480 animals in the four seasons of the year (autumn, winter, spring and summer), from March 2019 to February 2020. Two mussel samples were collected each season (n = 60) with average measurements of 23.9 mm for width, 33.8 mm for height, 69.9 mm for length, and 28.3 g for weight (shell + soft parts) in both coastal regions. Samples from Forno beach exhibited higher homogeneity in the winter for all evaluated parameters (width, height, length and weight). Mussel weight was the most variable parameter due to factors such as water flow, nutrients, and gonadal maturation stage. Regarding reproductive parameters, a predominance of females was observed at both beaches throughout all four seasons. Additionally, a predominance of both males and females at substage IIIA was observed during autumn and winter, while substage IIIC showed the highest presence in spring and summer. Keywords: Bivalve Mollusk; Growth indicators; Marine Biology; Reproduction